Foundations of psychological testing : a practical approach - Miller, Leslie A.; Lovler, Robert L. (Thousand Oaks Sage, 2020)
"Miller and Lovler's Foundations of Psychological Testing: A Practical Approach offers a clear introduction to the basics of psychological testing as well as to psychometrics and statistics. This practical book includes discussion of foundational concepts and issues, using real-life examples and situations students will easily recognize, relate to, and find interesting. A variety of pedagogical tools further the conceptual understanding needed for effective use of tests and test scores. The text aligns with the 2014 Standards for Educational and Psychological Testing. Key revisions to the sixth edition include updated references and examples, a new In Greater Depth box for deeper coverage of complex topics, and the reorganization of topics into a more manageable 14 chapter table of contents"--
Overview of psychological testing -- Psychometric principles -- Developing and piloting surveys and psychological tests -- Using tests in different settings -- Appendix A. Test spotlights -- Appendix B. Guidelines for critiquing a psychological test -- Appendix C. Code of fair testing practices in education -- Appendix D. Ethical principles of psychologists and code of conduct -- Appendix E. Table of critical values for Pearson product/moment correlation
Includes bibliographical references (pages 513-530) and indexes.
Keywords: Psychological tests